INTERNAL BELIEF OF THE JUDGE - Fatima H. Bajchorova (Вестник Северо-Кавказского федерального университета, 2022)
Article develops concept of proofs of criminal trial, estimates of proofs and internal prejudice. The author suggests to make changes in p.1 Art. 17 of the Code of criminal procedure of the Russian Federation, and gives the reasonings and arguments on the matter. The author focuses the main attention on "purity of judicial conscience", being guided which, on the internal prejudice the judge estimates proofs on criminal case